The effects of increasing doses of noradrenaline on systemic and renal circulations in acute bacteraemic dogs - Peng, Zhi-Yong; Critchley, Lester A. H.; Fok, Benny S. P. (Intensive care medicine, 2005)
To determine the dose-response effects of noradrenaline on the systemic and renal circulations during septic shock. Prospective controlled experiment in a university animal laboratory. Eight anaesthetized dogs. Transonic flow probes were surgically placed on the aorta via a left lateral thoracotomy and on the left renal artery. Blood pressure was measured from the femoral artery. Acute bacteraemia shock was induced by injecting Escherichia coli bacteria intravenously. Increasing doses of noradrenaline (0.1, 0.2, 0.3, 0.4, 0.5 microg kg(-1) min(-1)) were infused intravenously for 30 min at 30-min intervals. The model was first validated in four dogs. Mean arterial pressure, central venous pressure, cardiac output, and renal blood flow were measured. Systemic vascular resistance was derived. Induction of bacteraemia decreased mean arterial pressure, central venous pressure and systemic vascular resistance. Cardiac output slightly increased. Noradrenaline produced linear dose-dependent increases in both mean arterial pressure and systemic vascular resistance. The response was attenuated during bacteraemia. Under non-bacteraemic conditions the maximum dose of noradrenaline reduced the renal blood flow from 12+/-1 to 10+/-1 ml kg(-1) min(-1). Bacteraemia further reduced renal blood flow to 7+/-1 ml kg(-1) min(-1), which was partly restored by the maximum dose of noradrenaline to 11+/-3 ml kg(-1) min(-1). Noradrenaline can restore mean arterial pressure in bacteraemic shock and increases in mean arterial pressure are dose-dependent. The noradrenaline response is attenuated by bacteraemic shock. In bacteraemic shock noradrenaline also improves renal perfusion, as perfusion pressure increases. However, renal blood flow is not fully restored, suggesting that an element of impairment of renal blood flow exists due to the bacteraemia or noradrenaline.